2013
DOI: 10.5897/ajmr2013.5919
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the fermentation conditions for ethanol production by new thermotolerant yeast strains of Kluyveromyces sp.

Abstract: This study introduces two new thermotolerant strains of Kluyveromyces sp. for the biofuel industry to reduce the overall cost of production. The fermentation conditions including temperature, pH, incubation period and sugar concentration were adjusted. The two yeast strains were identified by sequencing of ITS1 and ITS2 regions. Comparing the sequence results with the GenBank reference proved that the strain Kluyveromyces sp. ZMS1 had 100% of similarity with Kluyveromyces maxianus. Yeast strain Kluyveromyces s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Narra et al [43] reported the use of a thermo-tolerant species of Kluyveromyces to hydrolyze and to ferment sugars obtained from cellulosic biomass to bioethanol. The observation in this study was in consonance with the previous report of Hashem et al [44] that mentioned a species of Kluyveromyces was used as the fermenting yeast in the production of ethanol. Other authors such as Saliu and Sani [33] and Abada et al [45] employed Saccharomyces cerevisiae to carry out the fermentation of hydrolyzed cellulolytic biomass to ethanol.…”
Section: Pre-treatment and Saccharification Of Plant Wastes To Hydrolysable Sugarssupporting
confidence: 93%
“…Narra et al [43] reported the use of a thermo-tolerant species of Kluyveromyces to hydrolyze and to ferment sugars obtained from cellulosic biomass to bioethanol. The observation in this study was in consonance with the previous report of Hashem et al [44] that mentioned a species of Kluyveromyces was used as the fermenting yeast in the production of ethanol. Other authors such as Saliu and Sani [33] and Abada et al [45] employed Saccharomyces cerevisiae to carry out the fermentation of hydrolyzed cellulolytic biomass to ethanol.…”
Section: Pre-treatment and Saccharification Of Plant Wastes To Hydrolysable Sugarssupporting
confidence: 93%
“…Our result is similar with the findings of Raikar (2012), where they observed maximum bioethanol concentration from grape after 48 hrs of fermentation at temperature 35 °C having broth pH 5.0. A similar study by Mohamed et al (2013) observed the highest ethanol concentration of 11.72% at 35 °C Kluyveromyces sp. after 96 hrs of fermentation period.…”
Section: Et Alsupporting
confidence: 68%
“…marxianus InaCC Y119 exhibited a higher ethanol yield than S. cerevisiae InaCC Y93 at 38°C during 48 h of fermentation. Another study (Hashem et al 2013) reported that Kluyveromyces sp. produces the highest ethanol content at 35°C after 48 h of fermentation.…”
Section: Prehydrolysis Simultaneous Saccharification and Fermentationmentioning
confidence: 99%